2003
DOI: 10.1177/0363199003256014
|View full text |Cite
|
Sign up to set email alerts
|

Love Riddles, Couple Formation, and Local Identity in Eastern France

Abstract: The purpose of this article is to show how specific aspects of the popular culture of Lorraine (eastern France) can be linked to distinctive features of the region's historical demography after the Thirty Years' War. It examines two customs associated with courtship: the dâyage, an exchange of riddle-like verses between groups of men and women at winter wakes, and the dônage, mock banns of marriage called by young men on the first Sunday of Lent. Both will be shown to have encouraged particularly high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Inspired by the work of Hasan-Rokem (2000; and Hopkin (2003; in re-evaluating von Sydow's (1932) concept of the ecotype, this study has shown that folk idioms or expressions are a fertile area of research that can be deconstructed using exhaustive literary and historical research based on the historic-geographic method. At the heart of this template, I would contend, is the need to read texts within their contemporary cultural, historical and socio-economic frameworks to decode meanings according to instantiation, the motivations for their use, and the question of agency in folk groups.…”
Section: O N C L U S I O N Smentioning
confidence: 95%
See 2 more Smart Citations
“…Inspired by the work of Hasan-Rokem (2000; and Hopkin (2003; in re-evaluating von Sydow's (1932) concept of the ecotype, this study has shown that folk idioms or expressions are a fertile area of research that can be deconstructed using exhaustive literary and historical research based on the historic-geographic method. At the heart of this template, I would contend, is the need to read texts within their contemporary cultural, historical and socio-economic frameworks to decode meanings according to instantiation, the motivations for their use, and the question of agency in folk groups.…”
Section: O N C L U S I O N Smentioning
confidence: 95%
“…At the heart of their argument was the claim that there is little difference between ecotypes and local sub-forms, although this largely ignores the influence of socio-cultural contexts or what von Sydow has termed "prevailing tastes." 8 Nevertheless in spite of such academic discord, a wide range of scholars have readily invoked the concept to deconstruct a range of folkloristic genres including rhyming couplets (Hopkin 2003), folksongs and folk ballads (Bošković-Stulli 1966;Cunningham 1976;Narváez 2002), folktales (Dundes 1962;Roberts 1966;Dégh 1972;Ballard 1983), fairy-tales (Dégh 1961), Wellerisms (Järviö-Nieminen 1959), personal narratives (Kalc̆ik 1975), legends (Ellis 1983) and 'urban legends' 9 (Brunvand 1974;Fine 1987;1992;Goldstein 1996;Ashton 2001). 10 In recent years, Galit Hasan-Rokem's (2000; innovative use of ecotypes to elicit 'the orality in the written' (Hasan-Rokem 2003: 2) in rabbinic literature has opened new perspectives on the interface of class, gender, culture, religion and ethnicity in Late Antiquity.…”
mentioning
confidence: 99%
See 1 more Smart Citation